2020
DOI: 10.2166/washdev.2020.051
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antimicrobial-resistant Escherichia coli in sewage treatment plants of South India

Abstract: Antibiotics received by sewage treatment plants may be the causative factor in spreading antibiotic resistance bacteria in the aquatic environment. The current study investigates the distribution of antimicrobial-resistant Escherichia coli (E. coli) in four sewage treatment plants (STPs) in South India receiving hospital and domestic wastewater in different proportions. A total of 221 E. coli isolates were checked for antimicrobial resistance against 16 antimicrobials. Among the antimicrobials tested, ampicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…However, this concentration is sufficient to develop antibiotic resistance in the bacterial populations due to selective pressure. This is supported by the recent studies done by Praveenkumarreddy et al 2020, where they found antibiotic resistant genes in the wastewater effluents of the treatment plants in southern India. In addition, the effect of low levels of pharmaceuticals and its toxicity on aquatic life forms requires further study.…”
Section: Resultssupporting
confidence: 54%
“…However, this concentration is sufficient to develop antibiotic resistance in the bacterial populations due to selective pressure. This is supported by the recent studies done by Praveenkumarreddy et al 2020, where they found antibiotic resistant genes in the wastewater effluents of the treatment plants in southern India. In addition, the effect of low levels of pharmaceuticals and its toxicity on aquatic life forms requires further study.…”
Section: Resultssupporting
confidence: 54%
“…Escherichia fergusonii isolates from spring water of Sikkim showed resistance to different classes of antibiotics including ceftazidime (73.33%), streptomycin (60%), ampicillin (60%), and cefoxitin (40%) ( Figure 4B). A similar study from Turkey found E. fergusonii isolates were resistant to penicillin G (100%), erythromycin (76.90%), and oxytetracycline (23%) (Parin et al, 2018). MDR E. fergusonii was also isolated from the Orissa (Mahapatra et al, 2009).…”
Section: Discussionmentioning
confidence: 82%
“…Antibiotic resistance is responsible for thousands of death annually and which is projected to increase dramatically as a global health hazard ( Momtaz et al, 2013 ; Adzitey, 2020 ). It is estimated that antibiotic resistance might lead to ten million deaths annually by 2050 ( Bengtsson-Palme et al, 2018 ; Praveenkumarreddy et al, 2020 ). Treatment of infectious diseases has been revolutionized since the discovery, production and use of antimicrobial substances ( Stange et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The propagation and spread of resistant pathogenic bacteria pose serious threats to the public heath for humans and animals [30,31]. It is estimated that antibiotic resistance may lead to 10 million deaths per year by 2050 [31].…”
Section: Discussionmentioning
confidence: 99%